2014
DOI: 10.1002/14651858.cd010115.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled steroids and risk of pneumonia for chronic obstructive pulmonary disease

Abstract: Analysis 5.1. Comparison 5 Sensitivity analysis-risk of bias, Outcome 1 Non-fatal serious adverse pneumonia events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
296
3
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(332 citation statements)
references
References 130 publications
12
296
3
15
Order By: Relevance
“…A 2014 Cochrane meta-analysis included 43 RCTs of at least 12 week's duration (FP 26 studies, n = 21,247; BUD 17 studies, n = 10,150) to assess the risk of pneumonia with ICS in COPD [Kew and Seniukovich, 2014]. The authors A re-analysis of the data shows a consistently increased risk of pneumonia after removal of the substantial statistical heterogeneity .…”
Section: Meta-analysesmentioning
confidence: 99%
“…A 2014 Cochrane meta-analysis included 43 RCTs of at least 12 week's duration (FP 26 studies, n = 21,247; BUD 17 studies, n = 10,150) to assess the risk of pneumonia with ICS in COPD [Kew and Seniukovich, 2014]. The authors A re-analysis of the data shows a consistently increased risk of pneumonia after removal of the substantial statistical heterogeneity .…”
Section: Meta-analysesmentioning
confidence: 99%
“…However, a recent study of a new LABA/ ICS combination containing fluticasone furoate found an excess of eight pneumonia deaths, seven in the group receiving the higher-than-recommended dose of this agent, suggesting that fluticasone itself may be particularly troublesome [24]. However, a recent meta-analysis did not exonerate budesonide [68].…”
Section: Safety Of Ics and Laba/ics In Copdmentioning
confidence: 99%
“…Interestingly, a systematic review that included 43 randomized clinical trials (over 30,000 patients) found that inhaled corticosteroids increase the risk of pneumonia and hospitalizations in patients with COPD but do not increase the all-cause mortality in these patients. 23 In summary, our study results show that in patients with CAP, those with COPD are sicker as assessed by severity of illness and co-morbidities. Yet these patients do not have worse short-term outcomes.…”
Section: Discussionmentioning
confidence: 56%